Development of an In Vitro Assay to Assess Pharmacological Compounds and Reversion of Tumor-Derived Immunosuppression of Dendritic Cells. (4th July 2021) - Andersen, Mikkel Møller; Larsen, Jesper; Hansen, Morten; Pedersen, Anders Elm; Gad, Monika
ABSTRACT: Background: Cancer immunotherapies have achieved much success and have become the forefront treatment of cancers previously associated with poor prognosis. However, a major challenge in cancer immunotherapies remains the heterogeneity of the immunoregulatory capacities of cancers, and not all patients of a given cancer responds to current therapeutic strategies. To address this issue and to facilitate the development of new pharmacological compounds, we here describe an in vitro model of dendritic cell suppression by cancer cells. Methods: We treated monocyte-derived dendritic cells with conditioned medium from cancer cell lines and assessed their maturation using ELISA and flow cytometry. In addition, we assessed their ability to induce T cell activation and differentiation. Results: We found that both the phenotypic and functional maturation of dendritic cells was suppressed by the conditioned medium. The expression of IL-12p70, TNF-α, CD80, CD83, and CD86 was significantly reduced by conditioned medium from the 786-O and HeLa cell lines, and CD4 + T cells had a weaker TH 1 phenotype with significantly decreased expression of IFN-γ and T-bet following co-culturing. Furthermore, we use our model to characterize the differential immunoregulatory capacities of primary cancers by using conditioned medium of cultured primary cancer cells. Conclusion: This model can be used to screen pharmacological compounds seeking to alleviate the immunosuppression of the tumor microenvironment and can furthermore be used to investigate the immunoregulatory capacities of primary cancer cells, which could be a helpful prognostic tool following tumor resection.